Appraising the motion for polyandry in the South African context through the selected episodes of Generations The Legacy - Montle, Malesela Edward (Penerbit Universiti Kebangsaan Malaysia, 2021)
The South African community has exuded a great interest in the suggestion for polyandry to be legitimised in the country. The year 2021 saw a rapid rise of inspirited debates and scholarly views on polyandry in South Africa. These scholarly and public engagements sought to conclude whether polyandry should be institutionalised in the country or not. Polyandry is a form of matrimonial union that entails one woman marrying or having two or more husbands. This kind of union has been exalted and cherished by several South Africans but also renounced by different opinionated citizens of the country. This paper has utilised a qualitative method to fulfil its main objective, which is to conceptualise and appraise the proposal for the recognition of polyandry in the South African society. It has employed a telenovela, Generations The Legacy, which has established a storyline that aided the researcher to explore polyandrous marriages and also comprehend South Africans’ attitudes, perceptions and reactions towards polyandry. Moreover, supplementary data was acquired from journal articles, magazines, newsletters and other social media platforms such as Twitter. The paper finds that polyandry is a relatively new phenomenon in the South African society and most of the predominant cultural assumptions discard it. Polyandry has been perceived as alien and tabooed by several citizens of the country in question, probably, by virtue of its threat to polygamy, which most South African are well acquainted with and have normalised. Therefore, it is the cultural conventions that strengthen the repudiation of polyandry today. The research implications of this paper include the focus on, enactment of specific polyandrous unions such as fraternal, associated, Nayar polyandries, and their fundamental assumptions on a broader scale.